(untitled) (2003)
In his book The Art of the Renaissance, Professor Fakhri Khalil continues his unique project of enriching the Arabic library by translating the best books published by major publishing houses in the world that chronicle the art of painting in particular and the visual arts in general, with a critical, documented, and solid history. These are, in order: - Dialogue of Vision (1987) - Impressionism (1987) - One Hundred Years of Modern Painting (1988) - Masterpieces of German Expressionism (1989) - One Hundred Years of Modern Architecture (1989) - Modern European Art (1990) - Modern Sculpture (1994) - Artistic Movements after World War II (1995) - From Da Vinci to Cézanne (2000) - Postmodern Art (2000). In this original book, which represents one of the most important stages in the history of the visual arts worldwide, Professor Fakhri Khalil excels as a translator, combining faithfulness to the text with a keen eye for conveying it to the Arabic reader in a language of fluent style, coherent structure, and precise vocabulary, so that the reader almost thinks the book was originally written in Arabic.
Title translation: The Art of the Renaissance- Murray, Peter and Linda; Tr: Khalil, Fakhri
Arabic
Keywords: N5300-7418 Visual Arts- History; Renaissance